CONTROL OF EGG HATCHER TEMPERATURE AND HUMIDITY WITH AIR AS A MATLAB-BASED CONTROL - mukhtar, agus (AutoMech : Jurnal Teknik Mesin, 2022)
AbstractEgg incubator on the market consists of three systems, namely manual, semi-automatic and automatic. The three egg hatching systems use water as a medium to control temperature and humidity in the hatchery. The use of water in the hatchery is very troublesome because it must always monitor the availability of water due to evaporation. In addition, the presence of water in the hatchery can invite mosquitoes to nest. For this reason, the author uses air as a medium to control temperature and humidity in the hatchery so that these things do not happen. In this study, analysis and simulation was carried out using Matlab software to find the best rise time value for the distance between the heating element and the egg rack so that the temperature on the egg rack was 38oC. In addition, an analysis of heat propagation from the heat source (heating element) to the egg rack was carried out using Solidworks software. Furthermore, an analysis of the air flow rate in the hatchery was carried out in the ventilation holes below and above the hatchery using solidworks software. After all the simulation data is obtained, a prototype is made to test the hatch percentage value on the egg incubator made. From the simulation results of the Matlab software, the distance between the heater and the egg rack is 11 cm, which has the best rise time value of 2.8 minutes. The simulation results from the Matlab software then simulated heat propagation using the Solidworks software on the egg rack to obtain a temperature of around 50oC. The simulation results of several air ventilation holes in the hatchery against the air flow rate obtained an even air flow rate in the hatchery. From the observation of the egg incubator prototype, the temperature was 38oC and the humidity was between 56% - 72% and the average hatching percentage was 28%. Keywords: Temperature, Humidity, Egg Incubator, MATLAB